The Wind Shifts : New Latino Poetry - Aragón, Francisco (Book collections on Project MUSE., 2007)
Authors included: Rosa Alcalá, Francisco Aragón, Naomi Ayala, Richard Blanco, Brenda Cárdenas, Albino Carrillo, Steven Cordova, Eduardo C. Corral, David Dominguez, John Olivares Espinoza, Gina Franco, Venessa Maria Engel-Fuentes, Kevin A. González, David Hernandez, Scott Inguito, Sheryl Luna, Carl Marcum, María Melendez, Carolina Monsivais, Adela Najarro, Urayoán Noel, Deborah Paredez, Emmy Perez, Paul Martínez Pompa, Lidia Torres.